Pengaruh Good University Governance dan Sistem Pengendalian Internal terhadap Kinerja Keuangan Perguruan Tinggi di Kota Palembang - Zelind Valensia Margaretha; Mutiara Maimunah (AKUNTANSI 45, 2026)
This study was conducted to examine the effect of good university governance and internal control systems on the financial performance of universities in Palembang City. The research employed a quantitative approach using primary data collected through questionnaires distributed to respondents from various universities. The population of this study consisted of universities in Palembang City registered in the Higher Education Database (PDDIKTI) and supervised by LLDIKTI Region II. The sampling technique applied was the saturated sampling method, in which the entire population was used as the research sample. As a result, 47 universities were selected with a total of 188 questionnaire responses collected; however, only 52 questionnaires met the criteria and could be processed further in the analysis stage. Data analysis and hypothesis testing were carried out using multiple linear regression analysis with the assistance of SPSS version 26. The findings of this study reveal that good university governance has a positive and significant effect on the financial performance of universities, indicating that effective governance practices contribute to better accountability, transparency, and institutional management. In addition, the internal control system was also found to have a positive and significant influence on financial performance, suggesting that strong internal supervision and control mechanisms are essential in supporting efficient financial management and improving the overall performance of higher education institutions in Palembang City.